1988
DOI: 10.1159/000185205
|View full text |Cite
|
Sign up to set email alerts
|

IgA Nephropathy and Henoch-Schönlein Purpura Nephritis with Anterior Uveitis

Abstract: Two patients with IgA nephropathy and a patient with Henoch-Schönlein purpura nephritis each associated with anterior uveitis are described. As anterior uveitis accompanying IgA nephropathy improved, renal manifestations were relieved. The patient with Henoch-Schönlein purpura nephritis suffered from not only anterior uveitis but also keratitis. It is suggested that immune mechanisms which induce IgA nephropathy may play a role in the development of anterior uveitis and keratitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 9 publications
(9 reference statements)
0
6
1
Order By: Relevance
“…Although the patient reported in the study of Kaur et al, [3] did not have any renal involvement, all of the three patients reported in the adult population had varying degrees of renal involvement [4,5]. Our patient had minimal lesions such as hematuria on microscopic evaluation and 1+ proteinuria on dipstick examination on the fourth week of the disease.…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…Although the patient reported in the study of Kaur et al, [3] did not have any renal involvement, all of the three patients reported in the adult population had varying degrees of renal involvement [4,5]. Our patient had minimal lesions such as hematuria on microscopic evaluation and 1+ proteinuria on dipstick examination on the fourth week of the disease.…”
Section: Discussioncontrasting
confidence: 45%
“…First our patient had bilateral anterior uveitis associated with HSP. The association of HSP and anterior uveitis was first described by Yamabe et al, [4]. The pathogenesis of uveitis in HSP is tought to be related of the pathogenesis of the main disease [8].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A literature review of ocular manifestations in HSP is summarized in Table 1. The most encountered ocular involvement was uveitis (n=4) [3][4][5][6], keratitis accompanied in two of these cases [3,4]. There are 2 cases of bilateral cystoid macular edema and cotton wool spots associated with decompensated HSP-related nephropathy [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…Ocular involvement has been very rare with only four reported cases of ophthalmological involvement. These include keratitis and granulomatous uveitis in one patient2 unilateral anterior ischaemic optic neuropathy3 bilateral central retinal artery occlusion4 and finally subperiosteal orbital haematoma 5…”
Section: Introductionmentioning
confidence: 99%